2017
DOI: 10.1111/jora.12315
|View full text |Cite
|
Sign up to set email alerts
|

An Explanatory Model of Dating Violence Risk Factors in Spanish Adolescents

Abstract: Dating violence is a serious public health issue that needs further understanding in terms of risk factors that may be involved in it. The main goal of this study was to test a mediational model of dating violence risk factors. The sample was composed of 477 secondary and college students from Spain (59% females). A dynamic developmental explanatory model considering aggressiveness, insecure attachment, interparental conflict, and peer dating violence was tested using a multigroup structural equation model. Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(53 citation statements)
references
References 53 publications
4
41
0
8
Order By: Relevance
“…In addition, violence within the couple also differs: it is usually reciprocal and less severe. Our results suggest that the youngest couples have the highest percentages in both victimization and perpetration, thus supporting the conclusions of most studies conducted with this type of population (Aizpitarte et al, 2017;Aizpitarte & Rojas-Solís, 2019;Cortés-Ayala et al, 2015;de la Villa et al, 2017;Pazos et al, 2014;Zamora-Damián et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, violence within the couple also differs: it is usually reciprocal and less severe. Our results suggest that the youngest couples have the highest percentages in both victimization and perpetration, thus supporting the conclusions of most studies conducted with this type of population (Aizpitarte et al, 2017;Aizpitarte & Rojas-Solís, 2019;Cortés-Ayala et al, 2015;de la Villa et al, 2017;Pazos et al, 2014;Zamora-Damián et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…It is worth noting that, when studying dating violence, there may be differences between adolescent couples and young couples. In fact, numerous studies focus on the violence that occurs in both types of couples (Cortés-Ayala et al, 2015;de la Villa et al, 2017;Pazos et al, 2014;Rubio-Garay et al, 2019); in young couples only (García-Carpintero et al, 2018;López-Cepero et al, 2015); and in adolescent couples only (Aizpitarte et al, 2017;Aizpitarte & Rojas-Solís, 2019;Zamora-Damián et al, 2018). In this sense, the relation between age and educational level should be taken into account; namely, as a general rule, adolescents are in the final phase of junior high school and in senior high school, and young people pursue higher education (college) courses.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the attachment dimension of avoidance, only two studies found a significant correlation between IPV perpetration and avoidance (Weiss et al, 2011 ; Aizpitarte et al, 2017 ), where other studies failed to replicate the same result. Correlational coefficients range from 0.30 to 0.13: as for anxiety dimension scores indicate a weak association between the two constructs.…”
Section: Resultsmentioning
confidence: 98%
“…Regarding sample types, researchers often used participants with no previous report of IPV such as students (Wigman et al, 2008 ; Grych and Kinsfogel, 2010 ; Gay et al, 2013 ; Tassy and Winstead, 2014 ; Ulloa et al, 2014 ; Aizpitarte et al, 2017 ; Gonzalez-Mendez et al, 2017 ; McClure and Parmenter, 2017 ) or minority population such as divorced couples (De Smet et al, 2012 , 2013 ) and jail population (Carraud et al, 2008 ). In this case, only four studies recruited participants with a previous reported history of IPV (Babcock et al, 2000 ; Genest and Mathieu, 2014 ; Muñoz, 2015 ; Pimentel and Santelices, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a sociocultural viewpoint, the peer group norms have been established as a risk factor due to their influence on the activation of aggressiveness (e.g., anger, hostile attitudes, and aggressive behaviors) (cf. Aizpitarte et al, 2017). Furthermore, these perspectives explaining the influences of peers on adolescents and young adults' lives are not necessary mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%